Low Cost Adsorbents for Sustainable Dye Containing-Wastewater Treatment - Ong, Siew-Teng; Keng, Pei-Sin; Lee, Siew-Ling; Hung, Yung-Tse (Asian Journal of Chemistry, 2014)
Dyes are coloured substances that can be applied to various substrates such as textile materials, leather, paper and hair. The usage of dyes has continuously increased in many industries but the removal of this pollutant remains as a problematic issue as they are generally stable to light and oxidizing agents and are resistant to aerobic digestion. This literature review paper provides and lists several low cost adsorbents to serve as an alternative method for dye removal. Adsorption using low cost materials can be viewed as a sustainable treatment process because most of these materials are of naturally occurring, locally available and inexpensive materials. This paper covers an overview of dyes waste treatments for 5 years period, from 2008-2012. Some of the noteworthy adsorbents include agricultural by-products, industrial waste and natural clay materials. Besides, the combination processes involving adsorption and other methods was also discussed.